2017
DOI: 10.1111/1752-1688.12567
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Signals from Rural Land Use and Exurbanization in a Mountain Landscape: What's Clear and What's Confounded?

Abstract: In mountainous landscapes with high climatic and geomorphic variability, how do rural land uses and exurbanization alter hydrology and water quality? We evaluated effects of rural land use and exurbanization on streamflows, suspended sediment concentrations and loads, specific conductance, and summer water temperatures in 12 streams and rivers within the Upper Little Tennessee River basin in the southern Appalachian Mountains. Eleven streams featured low levels of development (>61% forest cover) but differed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Other studies in the region have suggested that land use or land cover effects on other stream characteristics can be scaled up from local to regional scales (Price & Leigh, ; Scott et al, ). Conversely, regional studies of phosphorus and sediment export suggest that near‐stream vegetation is an important control on stream concentrations and export (Jackson et al, ; Scott et al, ). The difference can probably be attributed to differences in transport mechanisms and travel distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in the region have suggested that land use or land cover effects on other stream characteristics can be scaled up from local to regional scales (Price & Leigh, ; Scott et al, ). Conversely, regional studies of phosphorus and sediment export suggest that near‐stream vegetation is an important control on stream concentrations and export (Jackson et al, ; Scott et al, ). The difference can probably be attributed to differences in transport mechanisms and travel distances.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we estimated high flow using stream cross-section measurements and Manning's equation with the roughness factor calibrated from measured flows. These measurements were used to develop a discharge-stage height rating curve for each of the nine stream sites (Jackson, Bahn, & Webster, 2017). The three river sampling sites were co-located with USGS stream gages.…”
Section: Field Methods and Water Chemistry Analysismentioning
confidence: 99%
“…Evaluations of summer 2015 streamflows at two nearby U.S. Geological Survey gauges (Nantahala River, gage 03504000, 134 km 2 ; and Cartoogechaye Creek 03500240, 148 km 2 ) relative to long‐term median flows indicate that streamflows were typical, with baseflows decreasing from May to September, with numerous stormflow responses to summer thunderstorms. Other stream temperature studies in the area demonstrate that June–early September constitutes a sustained period of high summer stream temperatures (Jackson et al, ; Long & Jackson, ). Ideally, we would have collected data at every location in every stream for the entire summer, but we had a limited number of loggers, forcing us to follow a rotating schedule.…”
Section: Methodsmentioning
confidence: 95%
“…The regional climate is considered humid subtropical to marine humid temperate, with mild winters and summers (Webster et al, 2012). Precipitation in the study area is geographically variable, ranging from more than 1800 mm/year on the ridges to the southeast of the study area to 1,300 mm/year in the northeastern valleys of the study area (Clinton, ; Jackson, Bahn, & Webster, ; Price et al, ). Rainfall is evenly distributed throughout the year, and less than 5% of precipitation comes in the form of snow and ice (Swift & Messer, ).…”
Section: Methodsmentioning
confidence: 99%
“…Population is a main driver of land development and urban expansion due to the requirement of sufficient production and living spaces [74,75]. People gathered together will generate various human activities and cause serious ecological space disturbance by encroaching on the natural habitat of animals and plants or polluting the water and soil [76,77]. For example, urbanization and population are important driving forces of the morphological change of lakes and the conflict between rapid urban growth and the maintenance of water landscape is increasingly intensified [78].…”
Section: Major Influencing Factors Of Land Use Conflict In Yrebmentioning
confidence: 99%